All My Relations: Examining nonhuman relationships as sources of social capital for Indigenous and non-Indigenous youth 'aging out' of care in Canada - Doucet, Mélanie (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2020)
Objective: Provincial and territorial legislation across Canada mandates child welfare agencies to release youth from their care at the age of majority. Consequently, youth exiting care tend to have limited support networks, mostly comprised of formal and short-term connections. There is a gap in research examining long-term supportive relationships from the perspectives of youth who have 'aged out' of care. Methods: This PAR photovoice project involved 8 former youth in care ages 19 to 29 in Vancouver, B.C. over the course of 12 weeks, and entailed collaborative thematic analysis of the photographs. The lead researcher executed additional analysis following the data collection phase. Results: Relationships to culture, spirituality and the land were identified as important by racialized and Indigenous youth. Animal companions also emerged as an important non-human connection. Key barriers included a lack of culturally matched foster placements and social workers, gentrification, housing restrictions and a narrow definition of family relationships. Key strengthening factors included supportive community organizations and culturally responsive workers. Conclusion and Implications: Findings highlight the importance of including the relationships that matter to youth in care within child welfare decision-making and planning processes, and a need for systemic investment in long-term nurturing of those relationships. Connections that are outside of the traditional social capital framework for young people in care, such as non-human relationships, also need to be valued. By doing so, youth exiting care have a better chance at accumulating social capital and building a support network they can rely on during their transition to adulthood.